Different Influences of Two Peroxide Initiators on Structure and Properties of Poly(Lactic Acid). Issue 4 (27th January 2020) - Jiang, Wei; Ge, Xin; Zhang, Bangwen; Xing, Ruiguang; Chang, Mingming
Abstract : In the present work, poly(lactic acid) (PLA) was modified with two peroxide initiators: biphenyl peroxide (BPO) and dicumyl peroxide (DCP). The samples were all prepared with melt compounding method. Changes in the structure of PLA after the modification were analyzed with Fourier transformed infrared spectroscopy, gel penetration chromatography, and field emission scanning electron microscopy. Thermomechanical properties of the samples were determined with tensile test, dynamic mechanical analysis, and thermal gravimetric analysis/differential scanning calorimetry simultaneous thermal analyzer. Both BPO and DCP initiated free‐radical reactions at PLA polymer chains, which led to the formation of crosslinking structure. By this way, the tensile strength of PLA was elevated to about 50 MPa, which was much higher than the tensile strength of unmodified PLA (35.5 MPa). The glass‐transition temperature and melting temperature of the samples slightly decreased after modification. The different influences of BPO and DCP on PLA were mainly derived from their different chemical structures and activities.